Development of a BTB-/TBA(+) ion-paired dye-based CO2 indicator and its application in a multilayered intelligent packaging system - Lyu, Ji Sou; Chou, Inyoung; Hwang, Ki-Seob; Lee, Jun-Young; Seo, Jongchul; Kim, So Yeon; Han, Jaejoon (ELSEVIER SCIENCE SA, 2019)
Many visual indicators have been developed to provide product quality information through their incorporation into intelligent food packaging systems. In particular, the colorimetric changes undergone by the pH-sensitive dyes that are present in food packages can be used to monitor food quality without destroying the package. However, some difficulties remain in incorporating these dyes into commercial packaging materials because the dyes are often strongly hydrophilic, which leads to the migration of these dyes into food with high water contents through simple contact; additionally, these dyes do not easily mix with the hydrophobic polymers of packaging materials. To overcome these problems, we prepared a bromothymol blue (BTB-)/tetra-butylammonium (TBA(+) ) ion-paired dye and used it to produce a CO2-sensitive intelligent packaging film. Branched polyethylenimine was added to the indicator solution to improve the film's sensitivity to CO2. The formation of ion pairs was confirmed through Fourier transform infrared spectroscopy, and film characteristics, such as color changes in the presence of CO2 and thermal properties, were examined. Finally, we manufactured multilayered packaging films using the BTB-/TBA(+) ion-paired dye and used these to measure CO2 changes in kimchi packaging during the fermentation process. CO2- mediated color changes were easily visible to the naked eye, demonstrating the applicability of our sensor in commercial food packaging films.
Keywords: CARBON-DIOXIDE SENSORS; KIMCHI; PH; DISCRIMINATION; HEADSPACE; LABEL